A Model on Knowledge Workers Performance Evaluation - Nayeri, Mahmoud Dehghan (Review of Knowledge Economy, 2016)
The economic structure of society is constantly changing, whereas companies were dependent on manual labor in the past, today they are dependent on the knowledge worker. Since that knowledge workers make up two-thirds of the labor force, the focus of strategic plans nowadays are to improve their efficiency. Currently, there is not any adopted method for evaluating the performance of the knowledge workers. But the fundamental change in the nature of the labor force necessitates this issue. This paper aims to develop a model for evaluating the performance of knowledge workers in an Iranian research center using structural equation modeling, therefore this is a descriptive study based on co relational and regression analysis. Results proved that among the various appraisal criteria, innovation is the most important and significant factor which is equal to 4.35 in average from 5 and collaborate on research projects as well as attending seminars are the least important criteria according to the respondents point of view.